New Genre Arctic Art and Art Education Exhibition : Spectrum of Arctic Art Education:Näyttelyssä New Genre Arctic Art and Art Education - Manninen, Annamari; Terävä, Kuutti; Jokela, Timo (Stormen Concert Hall, 2024)
The video artistically presents a review of art and design education activities conducted within University of Lapland and the circles of the Arctic Sustainable Art and Design thematic network of UArctic (ASAD). The video is based on art education examples from past years carried out in collaboration with local communities, schools, artists, industries, and cultural institutes in Northern-Scandinavia. By showing glimpses of outdoor art projects in northern contexts, we aim to highlight how art education based on contemporary art and design can consider the unique conditions of northern and Arctic ecocultures, the opportunities provided by ecosystems, and cultural traditions. The video is structured according to the annual cycle of the year, illustrating how the eight seasons of the North, not only dominate but also enhance and improve art, design and art education practices. Such art is done by knowing and creating with eight seasons, with people of the North, their ecocultures by sustainable ways